STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH BATIK DI MADURA MELALUI HUMAN CAPITAL DAN PERAN QUADRUPLE HELIX - Dimas M Ghozali; Ahmad Budi Utomo; Moh. Toyyib (Kompetensi (Competence : Journal of Management Studies), 2017)
The economic potential possessed by Madura is so numerous from various sectors one of which is in the craft of Batik. However, the large number of people residing in Madura still has not given good hope to the community, especially in terms of economy. With such a vast territory and wealth possessed by Madura, this should be a business that results in improvement or development in a business venture. Factors that become obstacles and problems that often encountered are limited knowledge and capital. Therefore, it needs creative and innovative change as an effort to strengthen in economy. Human Capital is the hope of the whole society to be manifested as human with the support of the role of the surrounding community as a user of goods that the importance of awareness of the results of domestic production , the businessperson who is supposed to provide good business ethics, academics as an existing business development or conduct creative and innovative research in order to produce higher sales value and conduct training, mentoring and the role of government as a regulator must know the way of a good business venture . So with that, the effort will be done especially in batik will be a superior product in Madura. The existence of human capital and the role of quadruple helix in developing this business is expected to have the potential possessed by Madura can be processed optimally and more varied in batik business. With the existence of SMEs, the number of unemployed in Madura thinning and the stronger economy.